Study of Structural and Optical Properties of ZnS Nanoparticles - Vishwakarma, Kirti (Asian Journal of Chemistry, 2013)
In this paper, structural and optical properties of ZnS nano-particle have been synthesized by chemical method at room temperature. ZnS nanoparticles of different crystalline sizes have been synthesized by chemical route. The particle size is controlled by stirring rate, temperature of the solution, pH and time of stirring. The structural and optical characterization of the samples observed by XRD, TEM, UV-visible spectrophotometer and photoluminiscence show the formation of ZnS nanoparticle. A UV-visible optical spectroscopy study was carried out to determine the band gap of the nanocrystalline ZnS thin film and it showed a blue shift with respect to the bulk value. The room temperature photoluminescence spectra of the films showed two peaks centered.